Adsorption-induced slip inhibition for polymer melts on ideal substrates - Mark Ilton (Nature Portfolio, 2018)
When modeling fluid flow over a solid surface, one must determine the slip velocity at the boundary. Here Ilton et al. perform experiments to quantify the slip length of polymer melts at a nearly ideal solid surface and capture them in a model involving the density of physically adsorbed polymer chains.